PENGARUH PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK TERHADAP HASIL BELAJAR ASPEK KOGNITIF PESERTA DIDIK MATERI PENJUMLAHAN DAN PENGURANGAN PECAHAN KELAS V: PENELITIAN EXPOST FACTO - Fadelina Wizola Diva; Eko Kuntarto; Violita Zahyuni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to determine the effect of using the cooperative model of talking stick type on the learning outcomes of cognitive aspects of students in the addition and subtraction of fractions in class V. This research was conducted at SD Negeri 121/I Muara Singoan in the 2024/2025 academic year. With a sample of 16 students. The type of research is Quasi Experimental using the research design ‘pre-test and post-test one group design’, namely the research only uses one experimental class and there is no other class that is used as a comparison or control class. Data collection techniques were obtained by making observations about the activeness and collaboration of students and giving test questions to students before treatment then by giving test questions after treatment. Then the data was processed to compare activeness, collaboration and learning outcomes between before and after treatment. The results showed that there was a significant difference in the average final ability score of students' learning outcomes between before and after treatment. This is indicated by the results of the t test with the paired sample t-test obtained the value of t count greater than t table which is 8.883> 2.131. So Ho is rejected and Ha is accepted. Therefore, it can be concluded that there is a significant effect of the cooperative learning model of talking stick type on students' learning outcomes. From the results of this study, it can be concluded that the cooperative learning model of talking stick type has an effect on students' learning outcomes. Therefore, it is recommended for teachers and schools to strive for the use of learning by utilising the cooperative learning model of talking stick type because it improves student learning outcomes.